Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0001-3765201720160191
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Vibrio species isolated from estuarine environments (Ceará, Brazil) - antimicrobial resistance and virulence potential profiles

Abstract: Detection of virulent strains associated with aquatic environment is a current concern for the management and control of human and animal health. Thus, Vibrio diversity was investigated in four estuaries from state of Ceará (Pacoti, Choró, Pirangi and Jaguaribe) followed by antimicrobial susceptibility to different antimicrobials used in aquaculture and detection of main virulence factors to human health. Isolation and identification were performed on TCBS agar (selective medium) and dichotomous key based on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…were more diverse in brackish water sample than in freshwater sample. These findings corroborate some earlier reports and suggest that salt concentration modulates the diversity of vibrios in water resources ( Elhadi, 2013 ; Mookerjee et al, 2015 ; de Menezes et al, 2017 ; Fu et al, 2019 ). The result ( Figure 7 ; Supplementary Table SS1A ) of the present study showed that the possibility of contracting infections, such as cholera and cholera-like infections, caused by the non-halophilic vibrios is higher at the freshwater sampling sites most especially sites PA4, PA5, PA6, and ALD1 where most of the halophilic vibrios were recovered than at the brackish water sampling sites.…”
Section: Resultssupporting
confidence: 92%
“…were more diverse in brackish water sample than in freshwater sample. These findings corroborate some earlier reports and suggest that salt concentration modulates the diversity of vibrios in water resources ( Elhadi, 2013 ; Mookerjee et al, 2015 ; de Menezes et al, 2017 ; Fu et al, 2019 ). The result ( Figure 7 ; Supplementary Table SS1A ) of the present study showed that the possibility of contracting infections, such as cholera and cholera-like infections, caused by the non-halophilic vibrios is higher at the freshwater sampling sites most especially sites PA4, PA5, PA6, and ALD1 where most of the halophilic vibrios were recovered than at the brackish water sampling sites.…”
Section: Resultssupporting
confidence: 92%
“…[WHO], 2000). Vibrio alginolyticus and V. parahaemolyticus are resistant to penicillin and ampicillin (Menezes et al, 2017). Baticados et al (1990) have stated that some V. harveyi and V. splendidus are resistant to streptomycin, erythromycin, kanamycin and penicillin.…”
Section: Pseudoalteromonas Piscicida Exerts Antibacterial Activity Ag...mentioning
confidence: 99%
“…The first cases of V. parahaemolyticus gastroenteritis in Brazil occurred in 1975 and were caused by strain Cascavel, serotyped as O5:K17 (Hofer, 1983), which we had the opportunity to analyze in this study. Since 1975, there have been many reports on V. parahaemolyticus gastroenteritis outbreaks (Magalhães et al, 1991;Leal et al, 2008) and on the isolation of the bacterium from environmental sources in the country (Rojas et al, 2011;Ramos et al, 2012;Menezes et al, 2017). However, few studies have investigated the relationship between the pathogenic potential and genotype of these strains.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio parahaemolyticus is a Gram-negative halophilic bacterium, ubiquitous in estuarine and coastal waters, where it can be found free or in association with marine organisms, such as fish, shellfish, and zooplanktons (Baffone et al, 2006;Yu et al, 2013;Odeyemi, 2016;Lovell, 2017;Menezes et al, 2017;Narayanan et al, 2020;Parveen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation